ANALISIS MOTIVASI MENGAJAR GURU ATAS IMPLEMENTASI KURIKULUM MERDEKA DI SMP BHINA DHARMA 2 KOTA BANDUNG - Nugraha, Ios Susila (Universitas Tanjungpura, 2023)
This research aims to measure the level of motivation of teacher due to the implementation of Kurikulum Merdeka at SMP Bhina Dharma 2 Bandung. This is considered important because majority teachers are still confuse and lack of understanding to implement Kurikulum Merdeka, leading a decreasing level of motivation to teach. Meanwhile, motivation is an essential factor to improve teacher